5a^2-2ab-2b^2-(4a^2-2ab+b^2)要过程5a^2-2ab-2b^2-(4a^2-2ab+b^2)=[-3^2*2-(-2)^3*3-4*/6/]/(-3)^2=[-3^2*2-(-2)^3*3-4*/-6/]/(-3)^2,刚刚打错了是-6的绝对值

来源:学生作业帮助网 编辑:作业帮 时间:2024/10/07 01:06:32
5a^2-2ab-2b^2-(4a^2-2ab+b^2)要过程5a^2-2ab-2b^2-(4a^2-2ab+b^2)=[-3^2*2-(-2)^3*3-4*/6/]/(-3)^2=[-3^2*2-(-2)^3*3-4*/-6/]/(-3)^2,刚刚打错了是-6的绝对值
x)3M35JL5J24L\m OŲ۟Ƨ6Z8H (kgekokgUZ!c=r'ڞXk|VsaMR>q${q!v6C%pmQ]r6؂d B ]C m#]#M}K[]#<;om!&ކQ2 zg>;_h

5a^2-2ab-2b^2-(4a^2-2ab+b^2)要过程5a^2-2ab-2b^2-(4a^2-2ab+b^2)=[-3^2*2-(-2)^3*3-4*/6/]/(-3)^2=[-3^2*2-(-2)^3*3-4*/-6/]/(-3)^2,刚刚打错了是-6的绝对值
5a^2-2ab-2b^2-(4a^2-2ab+b^2)要过程
5a^2-2ab-2b^2-(4a^2-2ab+b^2)=
[-3^2*2-(-2)^3*3-4*/6/]/(-3)^2=
[-3^2*2-(-2)^3*3-4*/-6/]/(-3)^2,刚刚打错了是-6的绝对值

5a^2-2ab-2b^2-(4a^2-2ab+b^2)要过程5a^2-2ab-2b^2-(4a^2-2ab+b^2)=[-3^2*2-(-2)^3*3-4*/6/]/(-3)^2=[-3^2*2-(-2)^3*3-4*/-6/]/(-3)^2,刚刚打错了是-6的绝对值
=5a^2-2ab-2b^2-4a^2+2ab-b^2=a^2-3b^2
=(-18+24-24)/9=-2

5a^2-2ab-2b^2-(4a^2-2ab+b^2)=5a^2-2ab-2b^2-4a^2+2ab-b^2=a^2-3b^2
[-3^2*2-(-2)^3*3-4*/6/]/(-3)^2=(-18+24……?